Consequences of socialism in employee’s attitudes - Alas, Ruth (Journal of Business Economics and Management, 2003)
This paper compares people from former socialist countries with those of non‐socialist countries according to their attitudes toward society, trade unions, work and the organisations they work for ‐ based on empirical data from 15 countries. Results indicate that intrinsic factors of job satisfaction in the traditional capitalist countries have a greater correlation with feelings toward the company and general job satisfaction than extrinsic factors. The opposite is true of former socialist countries. Countries with a socialist past have to deal with the satisfaction of needs at a lower level than traditional capitalist countries and this consequently influences attitudes and expectations toward society, trade unions, organisations and work. First Published Online: 14 Oct 2010